Peran Pesantren dalam Membentuk Nilai Kewirausahaan dan Kepemimpinan Religius Santri - Lukman Hakim; Mohammad Abdul Khafid; Fahcrurriza Oktaviana Suyoto Putri (Al-Hayat Al-Istiqomah Foundation, 2019)
This research is a descriptive study with a qualitative approach which aims to describe the strategies carried out by Al Mawaddah Jekulo Kudus Entrepreneur Islamic Boarding School and Shofa Azzahro 'Gembong Pati Islamic Boarding School, Central Java, Indonesia in fostering entrepreneurial character and santri leadership. Data collection methods used consist of interviews, documents, and observations, methods of data analysis using data reduction, data presentation, and conclusion drawing. The results showed that the entrepreneurship activities of Al Mawaddah Jekulo Kudus Entrepreneurial Islamic Boarding School and Islamic Boarding School Shofa Azzahro 'Gembong went well. Likewise, the goal applied is that a santri must balance the life of the world and the hereafter. Because basically a santri must also think about the life of the world, not only those who are religious. The forms of entrepreneurship activities carried out are through training, dragon fruit cultivation, making chips from cassava, making Moka flour, syrup, sugar suppliers, cooperatives and umroh bureaus etc. The background of the activities carried out in Islamic boarding schools is to emulate the figure of the Prophet Muhammad who is a successful businessman figure and a form of modernization of learning activities in Islamic boarding schools in facing the challenges of the times. Entrepreneurship and leadership activities can be a medium in shaping the students to become independent individuals, stimulating creative ideas and intelligent communication with various groups.